Punitive actuarialism and the control of vehicle theft in Huánuco - Palli Calla, Cesar Fernando (2023)
Crime control, at present, is carried out under the approach of punitive actuarialism, which privileges the means rather than the end, and uses the logic of the market. Its manifestations have been incorporated in criminal laws with high penalties, through the classification of crimes of abstract danger; in procedural rules, through alternative ways out of the process and in criminal prosecution, abandoning the logic of case by case, to conduct prospective investigations, identifying crime hotspots to reduce them through strategies adopted by the prosecution and the police. This paper describes these ideas and applies them to a real case of vehicle theft, thus proving their concrete results in crime reduction statistics in the city of Huánuco.